Pain and disability : clinical, behavioral, and public policy perspectives - Osterweis, Marian; Kleinman, Arthur; Mechanic, David, 1936-; Institute of Medicine (U.S.). Committee on Pain, Disability, and Chronic Illness Behavior (Washington, D.C. : National Academy Press, 1987)
Evaluating claims based on pain poses problems for the Social Security Administration (SSA) and other disability insurers. This volume covers the epidemiology and physiology of pain; psychosocial contributions to pain and illness behavior; promising ways of assessing and measuring chronic pain and dysfunction; and clinical aspects of prevention.
The Ssa and Vocational Rehabilitation -- Measurement and Evaluation of Pain -- The Question of Mandatory Rehabilitation -- Research and Demonstration Projects -- References -- PART V CONCLUSIONS AND RECOMMENDATIONS -- 13 Conclusions and Recommendations -- RECOMMENDATION 1 DATA COLLECTION AT THE SSA -- RECOMMENDATION 2 NO NEW LISTINGS FOR PAIN OR ILLNESS BEHAVIOR -- RECOMMENDATION 3 SIGNIFICANT PAIN' SHOULD TRIGGER AN ASSESSMENT -- RECOMMENDATION 4 DEMONSTRATION PROJECTS -- Demonstration: The Feasibility and Consequences of Early Assessment -- Simple Assessment Tool -- Early Face-to-Face Hearing -- Integrated Functional Assessment -- Demonstration Project: Does Early Rehabilitation Work? -- Incentives and Disincentives for Rehabilitation -- The HHS Pain Commission's Proposal -- Demonstration Project for Early Rehabilitation -- Evaluation of the Demonstrations -- A Note About Research with Human Subjects -- RECOMMENDATION 5 RESEARCH AGENDA -- Epidemiological Initiatives -- Clinical Research -- Health Services Research -- Improved Methodology and Multidisciplinary Research -- RECOMMENDATION 6 EDUCATION TO IMPROVE THE CLINICAL CARE AND TREATMENT OF CHRONIC PAIN PATIENTS -- APPENDIX -- MYOFASCIAL PAIN SYNDROMES DUE TO TRIGGER POINTS -- MYOFASCIAL PAIN SYNDROMES: HOW COMMON ARE THEY? -- Why Are Myofascial Pain Syndromes So Common? -- HISTORICAL BACKGROUND -- NATURAL HISTORY -- DIAGNOSIS -- PERPETUATING FACTORS -- TREATMENT -- REFERENCES -- INDEX.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Chronic pain -- Social aspects; Chronic pain -- Government policy; Chronic pain -- Economic aspects; Disability evaluation; Chronic pain; Chronic diseases; Pain; Sick -- Psychology; Chronic Disease; Disability Evaluation; Pain; Public Policy; Sick Role; Douleur chronique; Invalidité -- Évaluation.; Douleur chronique -- Aspect social; Douleur chronique -- Politique gouvernementale; Douleur chronique -- Aspect économique.; Maladies chroniques; Douleur; Malades -- Psychologie; HEALTH & FITNESS -- Health Care Issues; MEDICAL -- Public Health; MEDICAL -- Health Policy; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Diseases; MEDICAL -- Health Care Delivery; Sick -- Psychology; Pain; Chronic pain; Chronic diseases; Chronic pain -- Social aspects; Disability evaluation